2016
DOI: 10.1371/journal.pone.0159235
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the BRAF mRNA Expression Level in Papillary Thyroid Carcinoma: An Analysis of The Cancer Genome Atlas Data

Abstract: BackgroundBRAFV600E is the most common mutation in papillary thyroid carcinoma (PTC), and it is associated with high-risk prognostic factors. However, the significance of the BRAF mRNA level in PTC remains unknown. We evaluated the significance of BRAF mRNA expression level by analyzing PTC data from The Cancer Genome Atlas (TCGA) database.MethodsData from 499 patients were downloaded from the TCGA database. After excluding other PTC variants, we selected 353 cases of classic PTC, including 193 cases with BRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Increased proliferation and cyclin activity are also hallmarks of cancer cells ( Chai et al., 2016a ), thus we aimed to characterize the expression of genes that have previously been shown to be up- or downregulated in thyroid cancer ( Agrawal et al., 2014 ; Chai et al., 2016b ; Costa et al., 2015 ; Wang et al., 2017 ). Interestingly, 72% of genes described as upregulated in thyroid cancer were downregulated in early passage (passage 0–2) organoids compared with primary tissue-derived cells, while some of these genes displayed further downregulation in later passage (passage 3–4) organoids ( Figure 4 A, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Increased proliferation and cyclin activity are also hallmarks of cancer cells ( Chai et al., 2016a ), thus we aimed to characterize the expression of genes that have previously been shown to be up- or downregulated in thyroid cancer ( Agrawal et al., 2014 ; Chai et al., 2016b ; Costa et al., 2015 ; Wang et al., 2017 ). Interestingly, 72% of genes described as upregulated in thyroid cancer were downregulated in early passage (passage 0–2) organoids compared with primary tissue-derived cells, while some of these genes displayed further downregulation in later passage (passage 3–4) organoids ( Figure 4 A, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high expression of MC in thyroid carcinoma appears to be a good marker for thyroid papillary carcinoma. BRAF somatic mutations, was the most extensively investigated molecular markers and common genetic alterations in PTC [ 51 ]. Many studies have found that higher expression of Braf mutant protein can predict aggressive tumor behavior in PTC, and BRAF V600E IHC has high practical value for the detection of the BRAF V600E mutation in primary and metastatic PTC [ 52 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact it is suggested that an overexpression of BRAF may contribute to an activation of the MAPK pathway,silencing of BRAF may induce a regression of melanoma xenografts in vivo . Furthermore, higher BRAF mRNA levels are associated with tumour malignancy regardless of possible mutations in this gene . Interestingly, feline ocular melanomas seem to result in a downregulation of BRAF , however, typical mutations found in human melanomas are not present in feline uveal melanomas.…”
Section: Discussionmentioning
confidence: 99%